A climatology of easterly waves in the tropical Western Hemisphere. (9th March 2017) - Belanger, J. I.; Jelinek, M. T.; Curry, J. A.
Abstract : To understand the relationship among easterly waves, tropical cyclones (TCs), and the large‐scale environment, a robust climatology of easterly waves for the tropical Western Hemisphere has been developed. The foundation for the climatology is a new easterly wave tracking algorithm that identifies westwards propagating disturbances over the tropical East Pacific, Atlantic, and Africa. To assess the issue of track dependencies and easterly wave representation, climatologies are prepared separately from the NCEP‐NCAR, CFS‐R, ERA‐40, and ERA‐Interim reanalyses. The source code for the easterly wave‐tracking algorithm along with the easterly wave climatology for each atmospheric reanalysis is publicly available from NOAA's National Centers for Environmental Information. Abstract : To understand the relationship between easterly waves, tropical cyclones and the large‐scale environment, a robust climatology of easterly waves for the tropical Western Hemisphere has been developed. The foundation for the climatology is a new easterly wave tracking algorithm that identifies westward‐propagating disturbances over the tropical East Pacific, Atlantic, and Africa. To assess the issue of track dependencies and easterly wave representation, climatologies are prepared separately from the NCEP‐NCAR, CFS‐R, ERA‐40, and ERA‐Interim reanalyses.